Prevalence and Diversity of Haemosporidian–Associated Matryoshka RNA Viruses in a Natural Population of Wild Birds - Carlos W. Esperanza; Caroline E. Faircloth; Scott W. Roy; Ravinder N. M. Sehgal (Ecology and Evolution)
ABSTRACT Matryoshka RNA viruses (MaRNAV) have recently been identified in association with haemosporidian parasites infecting both humans and birds, suggesting a potential role in host–parasite interactions. However, their prevalence, diversity, and ecological significance in avian hosts remain poorly understood. To address this knowledge gap, we investigated MaRNAV in wild bird populations in the San Francisco Bay Area. To investigate this, we examined blood samples from wild birds and birds undergoing rehabilitation in the San Francisco Bay Area. Samples were screened for haemosporidian parasite infections followed by RNA sequencing (RNAseq) and reverse transcriptase (RT) PCR to detect MaRNAV. Our analyses identified two novel MaRNAVs (MaRNAV‐5 and ‐6) in various bird species harboring diverse Haemoproteus and Leucocytozoon species. MaRNAV‐5, associated with Haemoproteus, exhibited 71.3% amino acid identity to MaRNAV‐4 and was found across 15 passerine species. MaRNAV‐6, linked to Leucocytozoon, shared 72.9% identity with MaRNAV‐3 and was found in 4 raptor species. The prevalence was 44.79% for MaRNAV‐5 in infected passerines and 22.22% for MaRNAV‐6 in infected raptors. These viruses were not found in uninfected birds and were consistently only in birds infected with haemosporidian parasites. Sanger sequencing revealed a high similarity of viral sequences across different bird species. Our findings indicate a notable prevalence of MaRNAV among local wild birds, suggesting potential impacts on their health and ecology. We discuss several hypotheses for the transmission and ecological role of these viruses in the context of haemosporidian parasite–host interactions. Further research is needed to determine the impact of these viruses on avian systems.